The New Gay News. (London : Gay News Publishing, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : veertiendaags
Redactie : Gay News, 5th Floor, 113/117 Farringdon Road, London ECIR 3 DQ ; vanaf (1983) 10 Lamb House, Church Street, London W4 2PH ; vanaf (1985) 42 Campden Hill Road 1, London W8
Voortzetting van Gay NewsWordt in [1986?] opgenomen in Gay Times
Engels
Periodiek